Analysis of Akbar Agra Fort (Journal of Architectural Design, 2023)
In given article we will try to analyze architecture of Agra Fort and it`s evolution process. Moreover, we will try to clear up the role of Akbar in formation of Baburid architecture. Lastly, we describe how Agra Fort buildings has been created and its development over the years, also, we have given evidence supporting our points